Hospital kanban system implementation: Valuating satisfaction of nursing personnel - Víctor G. Aguilar-Escobar; Sarah Bourque; Nicolás Godino-Gallego (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2015)
Literature on healthcare supply chain management has shown that the kanban system can provide significant benefits. However, very few benefits have been empirically demonstrated and the extent of each remains unknown. This study aims to measure nurses' satisfaction with kanban systems in logistics of medical consumables and assesses possible advantages and differences among user groups through an anonymous survey at Hospital Universitario Virgen Macarena of Seville, Spain. Treatment of responses included an exploratory factor analysis, and a CAPTCA analysis. The results showed a high level of satisfaction for each aspect of the kanban system. Moreover, it highlighted the differences of opinion between groups of individuals according to workplace, nursing units, job category, seniority, age and kanban training. The exploratory factor analysis revealed that two factors underlie the collected assessments: the inherent advantages of a kanban system, and the logistics system performance as a whole. Thus, hospital managers should promote the implementation of kanban systems, since it increases nurses' satisfaction and provides significant benefits.
Keywords: I1; M11; 330; Health; Kanban; Two-Bin System; Nursing; Hospital Logistics